Antagonistic and Synergetic Impacts of Conversation on Nonpersuasive Media Effects - Gehrau, Volker and Döveling, Katrin and Sommer, Denise and Dunlop, Sally (Communication Research, 2014)
This article elaborates the role of interpersonal communication in media effects. Based on an extensive literature review, two lines of arguments are illustrated: the antagonistic and the synergetic position. The literature provides theoretical and empirical support for both positions especially in the field of persuasive media input. To complete the view, two experiments with nonpersuasive media input are presented. The first experiment addresses the role of conversations in cognitive news effects. The synergetic position is supported: conversation leads to elaboration and more profound recall of media content. The second experiment deals mainly with emotional media effects in entertainment. No general impact of conversation on media effects was demonstrated. Nonetheless, the authors find evidence that conversations about the media engender a more critical and reserved stance toward the media content and protagonists. The article concludes with a discussion of the implications for further research into the field.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8wMDkzNjUwMjEyNDQ1NDgw